Novel Discrete Components based Speed Controller for Induction Motor - Hussain Attia; Ali Sagafinia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents an electronic design based on general purpose discrete components for speed control of a single phase induction motor drive. The MOSFETs inverter switching is controlled using Sampled Sinusoidal Pulse Width Modulation (SPWM) techniques with V/F method based on Voltage Controlled Oscillator (VCO). The load power is also controlled by a novel design to produce a suitable SPWM pulse. The proposed electronic system has ability to control the output frequency with flexible setting of lower limit to less than 1 Hz and to higher frequency limits to 55 Hz. Moreover, the proposed controller able to control the value of load voltage to frequency ratio, which plays a major parameter in the function of IM speed control. Furthermore, the designed system is characterized by easy manufacturing and maintenance, high speed response, low cost, and does not need to program steps as compared to other systems based on Microcontroller and digital signal processor (DSP) units. The complete proposed electronic design is made by the software of NI Multisim version 11.0 and all the internal sub-designs are shown in this paper. Simulation results show the effectiveness of electronic design for a promising of a high performance IM PWM drive.